Analysis of Student Hots in Solving Open Ended Problems for Functional Derivative Applications - Aida Ar Rohmah; Muhammad Anggito Mahathir Mukti; Restu Azahrah Fatmah; Slamet Soro (Urogram Studi Pendidikan Matematika, Universitas IVET, 2022)
Students are required to be more creative in solving mathematical problems that lead to High Order Thinking Skill (HOTS) thinking, namely applying the knowledge and skills of students that have been developed during learning. Open Ended Problem means a problem with various solutions and various solutions, so students are given the opportunity to think HOTS in solving Open Ended questions. This research was conducted with the aim of analyzing students' HOTS in solving Open Ended questions in learning mathematics. This type of research is a descriptive qualitative and case study approach. The subjects in this study were 4 class XII students of SMAN 64 Jakarta. The data collection technique used in this study is a written test of 5 questions with the help of Google Form. Based on the results of the research that students' HOTS can be determined by their ability to solve Open Ended Problems, the higher the level of ability in solving Open Ended Problems, the more HOTS indicators that students achieve. HOTS with high ability fulfills the indicators of analyzing (C4), evaluating (C5), and creating (C6). HOTS with moderate ability meets the indicators of analyzing (C4) and evaluating (C5). HOTS with low ability is only able to fulfill the analytical indicator (C4). Keywords: HOTS, Mathematics Ability, Open Ended Problem, Mathematics